SPASTIC FORM OF CEREBRAL PALSY, EPILEPSY WITH BENIGN EPILEPTIFORM DISCHARGE OF CHILDHOOD ON ELECTROENCEPHALOGRAM, AND IATROGENIC STEVENS–JOHNSON SYNDROME (CASE DESCRIPTION) - A. S. Kotov; M. N. Borisova; M. V. Panteleeva; A. V. Shatalin; E. O. Korobkina (Русский журнал детской неврологии)
The article describes the phenomenon of dual pathology – a combination of structural changes in the brain and benign epileptiform discharge of childhood on electroencephalogram. The uniqueness lies in the observation that the child, since birth suffering from spastic form of cerebral palsy and severe epilepsy, demonstrated the development of Stevens–Johnson syndrome due to intolerance of one of the antiepileptic drugs. Therapeutic approaches to overcome a whole range of violations are discussed in the article.